2010
DOI: 10.1186/1476-8518-8-4
|View full text |Cite
|
Sign up to set email alerts
|

PCEP enhances IgA mucosal immune responses in mice following different immunization routes with influenza virus antigens

Abstract: BackgroundWe previously demonstrated that polyphosphazenes, particularly PCEP, enhance immune responses in mice immunized subcutaneously and intranasally. The objective of the present study was to investigate the efficacy of polyphosphazenes as adjuvants when delivered through different routes of vaccine administration.MethodsBALB/c mice were immunized through intranasal, subcutaneous, oral and intrarectal delivery with vaccine formulations containing either influenza X:31 antigen alone or formulated in PCEP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Immunization with MPL and vaccine antigens has been shown to result in a mixed Th1 and Th2 or a shift toward either Th1 or Th2 response and it has been suggested that in addition to the route of administration, variables such as strains of the mice used, type of antigens as well as the concentration of antigen and MPL may affect the Th1/Th2 phenotype [25,26,39,42,43]. Baldridge et al [13] showed that hepatitis B and influenza antigens formulated with MPL and administered IN produced significantly higher IgG2a than IgG1, whereas tetanus toxoid mixed with MPL induced a lower IgG2a than IgG1.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with MPL and vaccine antigens has been shown to result in a mixed Th1 and Th2 or a shift toward either Th1 or Th2 response and it has been suggested that in addition to the route of administration, variables such as strains of the mice used, type of antigens as well as the concentration of antigen and MPL may affect the Th1/Th2 phenotype [25,26,39,42,43]. Baldridge et al [13] showed that hepatitis B and influenza antigens formulated with MPL and administered IN produced significantly higher IgG2a than IgG1, whereas tetanus toxoid mixed with MPL induced a lower IgG2a than IgG1.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many mucosal vaccine candidates fail to elicit strong antibody immune responses (67). Thus, there is a great need for mucosal adjuvants as they can break the tolerance and lead to enhanced immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when mice were immunized subcutaneously or intranasally using 50 µg of PCEP in combination with the influenza antigen X:31, PCEP stimulated enhanced production of IgG2a. 47 The same is true when mice received pertussis toxoid in combination with CpG, IDR and 10 µg of PCEP by subcutaneous route. 15 However, only little is known about the quality of the stimulated cellular immune responses following mucosal or parenteral vaccination using polyphosphazenes as adjuvant carrier system.…”
Section: Discussionmentioning
confidence: 89%